Developing endurance for sports performance - DiMenna, F. J.; Jones, A. M. (Strength and conditioning for sports performance, 2016)
When an exercise specialist suggests a training regimen for a client, it is not unlike the series of events that occurs when a doctor prescribes specific drugs for a patient. Indeed, because of this similarity, the design and delivery of an exercise programme that is individualised to a person`s needs is called exercise prescription. However, unlike a recommendation of pharmaceuticals that is based predominantly upon science, exercise prescription is one part science and an equal part art, because the appropriate course of action is often not nearly as well defined. This means that the savvy exercise specialist must use knowledge that is based upon sound scientific principle and apply it in a highly creative manner. The complex nature of exercise prescription is apparent when you consider the challenges associated with developing high-quality strength and conditioning (S&C) programmes for athletes who participate in distinctly different sports. For example, under the `track and field` umbrella term alone lie competitive performances as diverse as throwing a javelin, sprinting 400 metres, running 1,500 metres and completing a marathon. This means that athletes involved in these sports must train quite differently in order to hone the physiological attribute(s) necessary for success. Exercise prescription for athletes in different team sports is similarly challenging (e.g. hitting a cricket ball and running from wicket to wicket is much different from running the length of a football pitch and kicking a football) and further complicated by the fact that the physical demands of the sport are affected by contemporary strategic trends and prevailing rules and regulations. For example, in the early days American football, competitors `played both ways` (i.e. participated in both offence and defence) in every play of the game because, once they were removed, they were not allowed to re-enter. This changed when free substitution was legalised, which led to a platoon system where offensive players replaced defensive ones when a team gained possession of the ball. Once rosters were expanded, it became common for players to be rotated within offensive and defensive units depending upon the anticipated demands of the subsequent play and, indeed, the way the sport is currently contested, most players have highly specific roles (e.g. third-down back on offence, `nickel back` on defence). Conversely, although rugby appears similar in nature to American football, players are not permitted to re-enter a game once they are substituted for and, therefore, must remain active for prolonged periods. Consequently, physiological challenges are different for these athletes. Furthermore, the exertional demands that rugby players face during a game change considerably according to circumstances (e.g. a scrum or maul compared to open-field play), which means that a more diverse array of physiological attributes must be targeted during training. The need for diversity when training athletes for different sports is also apparent when you consider the physical requirements of basketball, ice hockey and football. While these sports appear similar (relatively long periods of play consisting of alternation of light, moderate and vigorous bouts of exertion), there are important differences which will affect prescription of a quality training regimen. Football does not allow free substitution, and play continues for extended periods across a very large playing surface, which means endurance is paramount. Stoppages are more frequent in basketball, free substitution is allowed (but only during stoppages in play) and the playing surface is much more confined. Consequently, although still considerable, the endurance requirement of this sport is less. Ice hockey is similar to basketball except substitutions can take place `on the fly`, which decreases the endurance requirement even further. However, this also allows for an increased intensity of effort during the shorter periods of time for which a player is active, which means that greater emphasis must be placed on different physiological attributes to prepare this athlete for the challenges he/she will face. With a thorough understanding of the extreme diversity suggested by the examples provided above, the exercise specialist must develop an exercise prescription consisting of an appropriate balance of power, speed and endurance training for athletes who rely to varying degrees on each of these attributes. A basic understanding of how the body`s energy systems interact is required for this process.